Logic, Computation, Hierarchies. - Brattka, Vasco; Diener, Hannes; Spreen, Dieter (Ontos mathematical logic., 2014)
<!Doctype html public ""-//w3c//dtd html 4.0 transitional//en""> Published in honor of Victor L. Selivanov, the 17 articles collected in this volume inform on the latest developments in computability theory and its applications in computable analysis; descriptive set theory and topology; and the theory of omega-languages; as well as non-classical logics, such as temporal logic and paraconsistent logic. This volume will be of interest to